In Addition to Stigma: Cognitive and Autism-Related Predictors of Mental Health in Transgender Adolescents. Issue 2 (4th March 2023) - Strang, John F.; Anthony, Laura G.; Song, Amber; Lai, Meng-Chuan; Knauss, Megan; Sadikova, Eleonora; Graham, Elizabeth; Zaks, Zosia; Wimms, Harriette; Willing, Laura; Call, David; Mancilla, Michael; et al.
ABSTRACT: Objective: Autism spectrum disorder (ASD) is significantly over-represented among transgender adolescents. Independently, ASD and gender diversity are associated with increased mental health risks. Yet, mental health in autistic-transgender adolescents is poorly understood. This study investigates mental health in the largest matched sample to date of autistic-transgender, non-autistic (allistic) transgender, and autistic-cisgender adolescents diagnosed using gold-standard ASD diagnostic procedures. In accordance with advancing understanding of sex/gender-related autism phenotypes, slightly subthreshold autistic diagnostic presentations (common in autistic girls/women) are modeled. Method: This study includes 93 adolescents aged 13–21, evenly divided between autistic-transgender, autistic-cisgender, and allistic-transgender groups; 13 transgender adolescents were at the margin of ASD diagnosis and included within a larger "broad-ASD" grouping. Psychological and neuropsychological evaluation included assessment of mental health, IQ, LGBT stigma, ASD-related social symptoms, executive functioning (EF), and EF-related barriers to achieving gender-related needs. Results: Autistic-transgender adolescents experienced significantly greater internalizing symptoms compared to allistic-transgender and autistic-cisgender groups. In addition to stigma-related associations with mental health, ASD-related cognitive/neurodevelopmental factors (i.e., poorer EF and greater social symptoms) were associated with worse mental health: specifically, social symptoms and EF gender barriers with greater internalizing and EF problems and EF gender barriers with greater suicidality. Comparing across all ASD and gender-related groups, female gender identity was associated with greater suicidality. Conclusions: Parsing the heterogeneity of mental health risks among transgender youth is critical for developing targeted assessments and interventions. This study identifies ASD diagnosis, ASD phenotypic characteristics, and EF-related gender barriers as potential risks for poorer mental health in transgender adolescents.